Five new records of Luvarus imperialis (Acanthuroidei: Luvaridae) in the south-west Atlantic Ocean - Domingues, R. R. [UNESP]; Montealegre-Quijano, S. [UNESP]; Soto, J. M. R.; Amorim, A. F. (Wiley-Blackwell, 2015)
Five new records of louvars Luvarus imperialis are documented for the south-west Atlantic Ocean, extending its distribution range in this ocean. The presence of one ripe specimen, associated with the previous records of larvae and juveniles, suggests that L. imperialis spawn in this region. The possible association of juveniles with shoals of skipjack tuna Katsuwonus pelamis is discussed. (C) 2015 The Fisheries Society of the British Isles
Keywords: feeding adaptation; louvar; pelagic fish; spawning area; uncommon fish